Conocimiento y cumplimiento de normas de bioseguridad en personal de salud de emergencia del Hospital Regional de Loreto-2022 - Tuesta Mejía, Jorge Lenner (2023)
This research was oriented towards the general objective of determining the relationship between the level of knowledge and the level of compliance with biosafety standards among emergency health personnel of the Regional Hospital of Loreto -2022. The study reviewed the background and theoretical basis referred to knowledge and compliance with biosafety standards in hospital environments. The study was observational, causal analytical and crosssectional. A sample of 100 participants was considered, including resident medical personnel, specialists and nurses from all shifts. A structured questionnaire was used for the variable of knowledge of biosafety standards, and an observation guide was used for the variable of compliance with biosafety standards. The results indicate that 75% of the sample has an average level of biosafety knowledge and 91% of the personnel consulted reported an average level of compliance with biosafety protocols. It was concluded that there is a positive association between the level of knowledge and compliance with biosafety standards among the health personnel in the sample (r=0.494, p=0.000<0.05). The dimensions of knowledge of clinical hand washing and hospital waste management were also significantly correlated with compliance with biosafety standards.